NEW PRIMER DESIGN of MULTIPLEX POLYMERASE CHAIN REACTION (PCR) for DETECTION of Escherichia Coli and Salmonella Enterica in FOOD SAMPLE - Hidayat, Muhammad Taufiq; Prayekti, Endah; Lukiyono, Yauwan Tobing; Romdhoni, Muhammad Afwan; Sari, Devi Fitriana (Program Studi Pendidikan Biologi FKIP Unpatti, 2024)
Background: Multiplex PCR techniques are used to detect multiple pathogens at the same time simultaneously. In order to achieve the specificity and sensitivity of detection, it is important to optimize the multiplex PCR method properly. Developing suitable primers and optimizing PCR temperature to boost particular genes from pathogens are key factors for this optimization. Methods: For the simultaneous detection of Escherichia coli and Salmonella enterica in food samples, this research aims to develop a set of primers for multiplex polymerase chain reaction (PCR). Using Primer-BLAST software, the study utilizes specific primer designs for the phoA gene (Eschericia coli) and invA gene (Salmonella enterica). DNA isolation has confirmed successful extraction from the two bacterial samples. PCR was performed under different conditions, including Singleplex and Multiplex PCR, using two annealing temperatures of 53oC and 50oC. Results: The results showed that this method can effectively amplify target genes and indicate their specificity and reliability at both temperature levels. Given these results, it has successfully conducted multiplex PCR using the built primer pairs. Both annealing temperatures of 50oC and 53oC can be used to perform multiplex PCR to detect E. coli and Salmonella enterica in one PCR reaction. Conclusion: Through this research, we have created a new set of Multiplex PCR Primers and an optimized multiplex PCR technique for the simultaneous detection of E coli and Salmonella enterica in food samples. The rapid and simultaneous screening of E. coli and S. enterica, which contributes to improved food safety measures and pathogen detection in the food industry, is promising with this optimized PCR approach.